Exploring Cross Cultural Understanding of an Indonesian Student Learning Abrod in Pakistan: A Narrative Inquiry - Dzulqoidah, Aulia; Rusmawaty, Desy; Kalukar, Ventje Jany (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2025)
This narrative inquiry study explores the experiences of an Indonesian student who studied abroad in Pakistan. This research aims to investigate the cross-cultural understanding of an Indonesian student studying in Pakistan through a narrative inquiry study. The study seeks to comprehend how their educational journey in a foreign country influences their perceptions of different cultures and how they navigate the process of cross-cultural adaptation. The study adopts a qualitative approach, utilizing in-depth interviews and reflective journal entries as primary data sources. Thematic analysis reveals that the student faced challenges such as culture shock, language barriers, and discrimination. However, the overall experience was positive, leading to a profound understanding of Pakistani culture and society. The study highlights the positive impact of intercultural experiences on personal growth, self-discovery, and the development of skills for effective collaboration with people from diverse cultures. The findings suggest avenues for further research, including enhancing intercultural competence, promoting effective collaboration in multicultural teams, managing culture shock, addressing stereotypes and misconceptions, fostering personal growth, and designing study abroad programs this research aims to contribute to the growing body of knowledge on cross-cultural understanding and adaptation among international students.